Economic evaluation of artesunate and three quinine regimens in the treatment of severe malaria in children at the Ebolowa Regional Hospital-Cameroon: a cost analysis. (December 2016) - Maka, Daniel; Chiabi, Andreas; Obadeyi, Bolaji; Mah, Evelyn; Nguefack, Séraphin; Nana, Pamela; Mbacham, Wilfred; Mbonda, Elie
Abstract Background Severe malaria is a leading cause of morbidity and mortality in under-fives in sub-Saharan Africa. Recently quinine has been replaced by artesunate as the first-line drug in the treatment of severe malaria in Cameroon. Artesunate has been shown to be cost-effective in African children, but whether these findings are transferable to Cameroonian children remains to be explored. Objectives To conduct a cost-analysis of four different regimens used in the treatment from the perspective of the healthcare payer. Methods An economic evaluation alongside a randomized comparative study was conducted in children aged 3 months to 15 years, admitted at the Ebolowa Regional Hospital with severe malaria due toPlasmodium falciparum. Patients were randomized to receive one of the four treatment alternatives. Group 1 (ARTES) received parenteral artesunate at 2.4 mg/kg at H0, H12, H24 and then once daily; Group 2 (QLD) received a loading dose of quinine base at 16.6 mg/kg followed 8 h later by an 8-hourly maintenance dose of 8.3 mg/kg quinine base; Group 3 (QNLD3) received 8.3 mg/kg quinine base every 8 h, and Group 4 (QNLD2) received 12.5 mg/kg quinine base every 12 h. The main outcome measure for effectiveness of treatment was the parasite reduction rate. Based on a healthcare perspective, an evaluation of direct medical costs was done, including costs of anti-malarials, nursing care materials, adjuvant treatment, laboratory investigations, hospitalisation and professional fees. Guided by a cost minimalization approach, the relative costs of these treatment alternatives was compared and reported. Results Overall cost was higher for ARTES group at 65.14 (95% CI 57.68–72.60) than for quinine groups (52.49–62.40), but the difference was not statistically significant. Cost of the anti-malarial drug was significantly higher for artesunate-treated patients than for quinine-treated patients, whereas cost of hospitalization was significantly lower for artesunate-treated patients than for quinine-treated patients. Incremental analysis of ARTES against QLD as a baseline resulted in an ICER of 46.8/PRR24 and suggests ARTES as the most cost effective of all four treatment options. Conclusion Artesunate is a cost effective malaria treatment option relative to quinine alternatives with the lowest incremental cost per unit of effectiveness. Trial registration clinicaltrials.gov identifier: NCT02563704. Registered 19 September 2015, retrospectively registered